PENINGKATAN SUMBER DAYA MANUSIA MELALUI PEMBERDAYAAN KEPEDULIAN SOSIAL, LINGKUNGAN SERTA EKONOMI MASYARAKAT KELURAHAN GUNUNG SAMARINDA KOTA BALIKPAPAN - Nina Indriastuty; Rihfenti Ernayani; Sa'ad Nico Arifin (Jurnal Abdi Masyarakat Ilmu Ekonomi (JAMIE), 2018)
Community service is one of the three pillars of higher education conducted by universities with the aim of contributing/helping to improve various community needs and solving various problems faced by the community so that the welfare of the community becomes increased. Although the implementation in the field is only 1 (one) month, the activity provides many benefits to the residents of Gunung Samarinda Village and University of Balikpapan's third wave KKN students. Among other things, the service that has been carried out provides education to the public regarding environmental hygiene, concern for the environment, utilization of waste that can generate economic value and concern for the community to live a healthy life.